Pengaruh Etos Kerja dan Disiplin Kerja Terhadap Peningkatan Kinerja Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Serang - Saehumillah, Saehumillah; Sutoto, Sutoto (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Based on the results of data analysis and processing by researchers at the BPKAD of Serang Regency, there are still weaknesses/shortcomings such as the insufficient number of human resources for a BPKAD in Serang Regency, which has a large responsibility, the low level of employee responsibility, low discipline rates, weak fairness among employees, inadequate job execution, and lack of initiative. The approach in this research is a quantitative approach. According to Sugiyono (2020:16), data collection uses research instruments, and data analysis is quantitative/statistical in nature, with the aim of testing the established hypothesis. Using Variable Operationalisation where Employee Work Ethos (X1), Work Discipline (X2), and Employee Performance (Y). The instrument test conducted is using a validity test to acknowledge the research's validity. Based on the explanation in the previous chapter, for this validity test, a questionnaire was distributed to 30 respondents (n30). Thus, based on the product moment table, the critical value (rkritis) obtained is 0.361. With the provision that the instrument is said to be valid if rhitung is greater than rkritis, and if rhitung is less than rkritis, then the instrument is declared invalid. Here are the results of the validity test of the research instruments for Variable X1 (Work Ethos), X2 (Work Discipline), and Variable Y (Employee Performance). BPKAD Serang Regency, although the education level of the ASN is quite high, this has not yet fully reflected in optimal discipline, motivation, and work responsibility. The research results indicate that there are still weaknesses in aspects of work behaviour such as responsibility and discipline that affect the achievement of employee performance targets.